Concept Analysis of Self-Care Strategies in Schizophrenia - Dessy Dwi Cahyaningrum; Meidiana Dwidiyanti; Titik Suerni (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Schizophrenic patients will experience an inability to care for themselves. This has an impact on cognitive impairment. Therefore the self-care strategy of schizophrenic patients is very important and must be assessed by nurses regularly. The purpose of this paper is to analyze the concept, clarify the meaning of the concept of self-care strategies in schizophrenia. The concept analysis procedure from Walker and Avant is used in this paper. Literature reviews are conducted using online databases, such as Sciencedirect, Pubmed, Google Scoolar and the scientific journal of health, with the keywords